Perikatan atau Persetujuan dan Jaminan terkait Kearifan Lokal Tentang Budaya Matamusan di Kabupaten Malaka - Faustino Paskalis Gles Natel; Ledythria Fernanda Maia; Antonius Dolu Fransiskus Andi Tan; Castyelo Yohanes A. Sogen; Claudio Xaverius Oematan; Yohanes Bendito Mitang (Universitas Sains dan Teknologi Komputer, 2024)
Malaka is one of the districts in Indonesia. The people of Malaka Regency generally adhere to a matrilineal marriage system. The method used in this research is an empirical method. The traditional matrilineal marriage legal system only exists in two districts, namely Malaka District and Ngada District. Each customary marriage legal system has its own unique character. Mata Musan is a hereditary custom passed down from generation to generation. The Mata Musan tradition itself has many positive values ​​that can be taken away by today's generation.